FDI and poverty in-line with quality of governance and voice and accountability: Follow-ups based on linear and non-linear ARDL - Khawaja Asif Mehmood (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
The aim of this study is to explore if effects of Foreign Direct Investment (FDI) alone on poverty in Pakistan during the time period of 1980 to 2022 are different from those with internal precursors like quality of governance and voice and accountability. For the estimation of effects of FDI on poverty, Linear Autoregressive Distributed Lag (ARDL) as well as Non-Linear ARDL (NARDL) are used. The originality of the study depends on the ascertain that FDI alone and as an interaction with private investment, quality of governance, and voice and accountability is explored to locate if the affectations are dissimilar on poverty. FDI is found to be unfavorable for poverty alleviation. The findings are even trivial when used with private investment. However, the effects of FDI as an interaction term with quality of governance and voice and accountability are positive and significant in mitigating poverty. The government is suggested to acquire appropriate quality of governance and voice and accountability in complementary with FDI to address the rising poverty.
Keywords: 330; Poverty; FDI; private investment; quality of governance; voice andaccountability; Pakistan